The ECU as the future currency of financial transactions - Sinimaaria Ranki (Bank of Finland, 1993)
The paper presents the development of the role of the ECU in the financial markets. The ECU is the only currency basket to have developed as a currency. It has gained popularity for several reasons. In the early 1980s, the most important reason was that it offered a simple, easy and inexpensive way to diversify exchange rate risk. In the 1990s, the main driving force was the expectation of a European Economic and Monetary Union with the ECU as the single currency. However, the crisis in 1992 caused sever uncertainty about the future of the monetary union. As a consequence, the ECU market suffered, and the risk diversifying properties of the ECU have regained importance. Because the monetary union' depends to a large extent on the functioning of the European Monetary System (EMS), a credibility test of selected EMS exchange rates is conducted. The results suggest that, despite of achieved inflation rate convergence, the stability of the EMS is not self-evident. The (political) willingness of the participating countries to follow an anti-inflationary policy during a recession is also important. If one of the countries gives signs of devaluaing or perhaps leaving the system, uncertainty of the future of the EMS is quickly spread. This, in tum, is reflected in the use of the ECU. Hence, the creditworthiness of the ECU is dependent on the credibility of the EMS as a system. Finally, future prospects for the ECU are discussed. The main point is that in the short term, some preconditions for the efficient use of the ECU must be fulfilled. Firstly, the Maastricht Treaty must be ratified and the EMU put back on track. Secondly, remaining legal obstacles to ECU usage must be removed. Thirdly, the ECU payment systems must be reinforced. Finally, governments must set an example in using the ECU as money. Only then will investors realize that the way has been cleard for the ECU to become the single currency of the EC. In the long term, in tum, only the EMU will make the ECU a major world currency.
URN:NBN:fi:bof-201908121391
Keywords: 330